(3GSJNOGe JcfhdhLjG GdeYdheGJ dJjSjQ ELQGAGJ GdJbGVj GdeOfj (B:s (3OQGSI ebGQfI (B/s - (3eMeO, eMehO eNJGQ YHO GdeZjK,s 1983- ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2013)
(3jJfGhd cJGH (B((3GSJNOGe JcfhdhLjG GdeYdheGJ dJjSjQ ELQGAGJ GdJbGVj GdeOfj (B: (3OQGSI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3eMehO eNJGQ YHO GdeZjK eMeO(B) (3aj MhGdj (B(272) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3eYGdLI HjGfGJ aj GdbVGA GdeOfj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdeHMK GdChd (B: (3eGgjI GSJNOGe JcfhdhLjG GdeYdheGJ dJjSjQ ELQGAGJ GdJbGVj, GdeHMK GdKGfj (B: (3ebJVjGJ JcfhdhLjG GdeYdheGJ dJjSjQ ELQGAGJ GdJbGVj GdeOfj, GdeHMK GdKGdK (B: (3fWGb GSJNOGe JcfhdhLjG GdeYdheGJ dJjSjQ ELQGAGJ GdJbGVj GdeOfj(B.s
(3edGMb (B: (3UaMI (B225-245.s
(3HHdjhLQGajI (B: (3UaMI (B246-263.s
Keywords: (3GdbVGAs -- (3eYGdLI GdHjGfGJs; (3bGfhf GdELQGAGJ GdeOfjI hGdJLGQjIs -- (3eUQs -- (3eYGdLI HjGfGJs; (3GdOYhi GdeOfjIs -- (3eUQs -- (3eYGdLI HjGfGJs; (3GdJbGVj GdeOfj s; (3GdeMceI GdeOfjI GdEdcJQhfjIs